1996
DOI: 10.1007/bf00409413
|View full text |Cite
|
Sign up to set email alerts
|

Toluene itself as the best urinary marker of toluene exposure

Abstract: Head-space gas chromatography (GC) and high-performance liquid chromatography (HPLC) (with fluorescence detectors) methods were developed for toluene (TOL-U) and o-cresol (CR-U) in urine, respectively. In order to identify the most sensitive urinary indicator of occupational exposure to toluene vapor (TOL-A) among TOL-U, CR-U, and hippuric acid in urine (HA-U), the two methods together with an HPLC (with untraviolet detectors) method for determination of HA-U were applied in the analysis of end-of-shift urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
0
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 16 publications
10
61
0
1
Order By: Relevance
“…The high correlations between airborne and urinary VOCs are consistent with the previously reported data [14,4,6,7]. The comparative evaluation of toluene exposure showed that in the low range of exposure concentrations, TOL-U can be considered a better biomarker of exposure than BA-U and o-cresol in urine.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The high correlations between airborne and urinary VOCs are consistent with the previously reported data [14,4,6,7]. The comparative evaluation of toluene exposure showed that in the low range of exposure concentrations, TOL-U can be considered a better biomarker of exposure than BA-U and o-cresol in urine.…”
Section: Discussionsupporting
confidence: 90%
“…The data on the relationship between VOC concentrations in the air and concentrations of unchanged compounds in blood and for toluene, ethylbenzene, xylene and mesitylene varied from 0.45 h to 0.88 h for phase I and from 6.7 h to 19.2 h for phase II [2]. The data reported recently for exposure in occupational setting show that the determination of unmetabolized solvents in urine provides a highly sensitive and specific index of exposure to VOCs [3][4][5][6][7][8][9][10][11]. The purpose of the present study was to compare the validity of various biomarkers of exposure to toluene, ethylbenzene and xylene at low levels of occupational exposure and to find out whether the determination of unchanged VOCs in urine would be useful for the assessment of exposure around and below the current occupational exposure limit.…”
Section: Resultsmentioning
confidence: 95%
“…The method employed was basically as previously described (Kawai et al 1996). In practice, a gaschromatogram (5890 Series II, Agilent Technologies, Santa Clara, CA, U.S.A.) with a flame-ionization detector (FID) was connected with an automated head-space air sampler (HP7694, Agilent Technologies, Santa Clara, CA, U.S.A.) and equipped with a polar column of DBWAX (Agilent Technologies, Santa Clara CA, U.S.A.) (60 m, 0.53 mm and 1.0 μ m in length, inner diameter and film thickness, respectively).…”
Section: Analytical Instruments and Conditionsmentioning
confidence: 99%
“…The use was not limited to occupational health where the method was originally developed [1][2][3][4][5][6] , but also in environmental health fields 7,8) . The method has been applied to analysis for un-metabolized mother chemicals 1,[9][10][11][12] as well as for metabolites after proper automated derivatization of metabolites to increase volatility [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…With the improvement of analytical methods, unmetabolized VOCs in urine were again paid much attention from 1990 onwards, mainly by Japanese researchers. Good correlations between air and urinary toluene, xylenes and styrene have been reported in occupational environments with over 0.1 ppm solvent exposure [12][13][14][15][16][17][18][19][20][21][22][23] . 6) .…”
mentioning
confidence: 99%